Shifts, Trends, and Drivers of Lake Color Across China Since the 1980s - Zhigang Cao; John M. Melack; Miao Liu; Tiit Kutser; Hongtao Duan; Ronghua Ma (Geophysical Research Letters, 2023)
Abstract Lakes are sentinels of global changes and integrators of processes in watersheds. Changes of lake water quality can be observed in shifts in lake color, however, the prevalence of shifts and trends in color and relevant factors remain elusive. Here, a comprehensive examination of color in 2,550 Chinese lakes from 1984 to 2021 revealed that color in 68% of the lakes shifted toward shorter visual wavelengths. Lakes in the Tibetan Plateau had larger declines in wavelength than lakes in other areas. The factors associated with reduced visual wavelengths varied in different ecoregions. A warmer and wetter climate in deep lakes in western China is associated with shifts toward blue. Increased vegetation in watershed and decreased wind are associated with green‐yellow shifting to green‐cyan color in shallow lakes of eastern China. Our study highlights the heterogeneous controls of climate and humans on changing patterns of lake colors.